Teacher’s mental health during the Covid-19 pandemic (Research, Society and Development, 2022)
The pandemic caused by the new coronavirus brought numerous changes in the lives of the entire world population in the year 2020 and 2021, including the need to adapt to remote work. The category of teachers was one of those directly affected by this phenomenon. This article aims to analyze how teachers from a municipal public school in the city of Uberaba-MG who experienced the reality of adapting their work from face-to-face classes to remote classes and how this led to the emergence and/or worsening health and teaching work. For this, an exploratory descriptive research was carried out in the repositories of publications of articles and essays by electronic means and with the teachers we used a semi-structured online questionnaire in which the participants answered questions related to mental health in the midst of the circumstances generated by the new lived context and, later, a bibliographic analysis of the constructed data. As a result, we have a sample of teachers who went through a period of fragility and affectations in their mental health due to all the changes in the dynamics and conditions of the work available to exercise their teaching, and situations arising from this traumatic period of the Covid-19 pandemic generated in the personal and professional life here in the cut of the personal and professional life of teachers.